IMPLEMENTATION OF PUBLIC SERVICES FOR STATE NAVIGATION VESSELS IN MAINTENANCE OF NAVIGATION AIDS IN BITUNG TYPE A CLASS I NAVIGATION DISTRICT - Nicholas Adventure Indrianto Ho; Jetty E. H. Mokat; Devie S. R. Siwij (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the implementation of public services for the shipping of the State Ship (KN) Miangas in supporting the maintenance of Navigational Aids (SBNP) in the Bitung Class I Type A Navigation District , and to identify the supporting and inhibiting factors for the effectiveness of the shipping as an instrument of public navigational services. This study uses a qualitative approach with a descriptive research type. The research location was conducted in the Bitung Class I Type A Navigation District . Research informants were determined by purposive sampling , including the Head of the Navigation Section, the Captain of the KN Miangas, and the SBNP Maintenance Technical Officer. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman (data reduction, data presentation, conclusion drawing). Data validity was tested by triangulation of sources, techniques, and time. The results of the study indicate that the shipping of the KN Miangas is quite effective in supporting the maintenance of SBNP, but not yet fully optimal.